Voluntary running in mice beneficially modulates myocardial ischemic tolerance, signaling kinases, and gene expression patterns - Budiono, B.; See Hoe, L.; Peart, J.; Sabapathy, S.; Ashton, K.; Haseler, Luke; Headrick, J. (2012)
Exercise triggers hormesis, conditioning hearts against damaging consequences of subsequent ischemia-reperfusion (I/R). We test whether "low-stress" voluntary activity modifies I/R tolerance and molecular determinants of cardiac survival. Male C57BL/6 mice were provided 7-day access to locked (7SED) or rotating (7EX) running-wheels before analysis of cardiac prosurvival (Akt, ERK 1/2) and prodeath (GSK3ß) kinases, transcriptomic adaptations, and functional tolerance of isolated hearts to 25-min ischemia/45-min reperfusion. Over 7 days, 7EX mice increased running from 2.1 ± 0.2 to 5.3 ± 0.3 km/day (mean speed 38 ± 2 m/min), with activity improving myocardial I/R tolerance: 7SED hearts recovered 43 ± 3% of ventricular force with diastolic contracture of 33 ± 3 mmHg, whereas 7EX hearts recovered 63 ± 5% of force with diastolic dysfunction reduced to 23 ± 2 mmHg (P < 0.05). Cytosolic expression (total protein) of Akt and GSK3ß was unaltered, while ERK 1/2 increased 30% in 7EX vs. 7SED hearts. Phosphorylation of Akt and ERK 1/2 was unaltered, whereas GSK3ß phosphorylation increased ~90%. Microarray interrogation identified significant changes (=1.3-fold expression change, =5% FDR) in 142 known genes, the majority (92%) repressed. Significantly modified paths/networks related to inflammatory/immune function (particularly interferon-dependent), together with cell movement, growth, and death. Of only 14 induced transcripts, 3 encoded interrelated sarcomeric proteins titin, a-actinin, and myomesin-2, while transcripts for protective actin-stabilizing ND1-L and activator of mitochondrial biogenesis ALAS1 were also induced. There was no transcriptional evidence of oxidative heat-shock or other canonical "stress" responses. These data demonstrate that relatively brief voluntary activity substantially improves cardiac ischemic tolerance, an effect independent of shifts in Akt, but associated with increased total ERK 1/2 and phospho-inhibition of GSK3ß. Transcriptomic data implicate inflammatory/immune and sarcomeric modulation in activity-dependent protection. © 2012 the American Physiological Society.